USAHA GURU PENDIDIKAN AGAMA ISLAM MENGEMBANGKAN POTENSI EMOSIONAL SISWA DALAM MENINGKATKAN PROSES PEMBELAJARAN (STUDI DI SMP N 29 PADANG) - Silvia Susrizal (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
This study was conducted because of the need for the development of the emotional potential in the learning process conducted by teachers of Islamic Education at SMP N 29 Padang. The purpose of this study is to determine the efforts undertaken by teachers of Islamic Religious Education develop the emotional potential of students in improving the learning process. The research method used is field research is descriptive. In this research has not seen efforts of Islamic religious teachers in developing the emotional potential of their students, including indication is that students have not yet felt a really enjoyable learning atmosphere such as learning PAIKEM, but instead students feel the lack of learning atmosphere, full of uneasiness, Not well developed and maximal.